Reflections of Elementary School Literacy Coaches on Practice: Roles and Perspectives - Lynch, Jacqueline; Ferguson, Kristen (Canadian Journal of Education/Revue canadienne de l'éducation, 2010)
In this study, we examined the perceptions of Ontario elementary (primary K – 3 and junior 4 – 6) literacy coaches to determine their roles, beliefs, and practices. We inter‐ viewed thirteen literacy coaches working in one Ontario school board about their literacy coaching. All coaches interviewed were teachers with specialized experience working in a literacy intervention program in their school board. We identified three major topics in participants’ statements: coaches’ role, barriers to effective literacy coaching, and overcoming barriers. This research offers suggestions for change in practice and provides insight into the role of literacy coaching as a mode of profes‐ sional development in a Canadian urban centre. Key Words: professional development, primary/junior teachers, literacy, elementary schools, Ontario education Dans cette étude, les auteures analysent les perceptions de formateurs en littératie (maternelle, primaire, premier cycle du secondaire) en vue de mieux cerner leurs rô‐ les, leurs croyances et leurs pratiques. Elles ont interviewé treize de ces formateurs à l’œuvre au sein d’une commission scolaire ontarienne, tous des enseignants ayant acquis une expérience pointue dans le cadre d’un programme d’intervention en litté‐ ratie. Les auteures ont identifié trois grands thèmes dans les propos des participants : le rôle des formateurs, les obstacles auxquels font face les formateurs en littératie et les méthodes employées pour surmonter les obstacles. À la lumière de leur recherche, les auteures proposent des suggestions de changements à apporter dans les pratiques ainsi que des réflexions sur le rôle du formateur en littératie dans le perfectionnement professionnel au sein d’un centre urbain canadien. Mots clés : perfectionnement professionnel, enseignants du primaire et du premier cycle du secondaire, littératie, écoles primaires, éducation en Ontario.